When Journalism and AI intersect: Effects on Professional Ideology - Spyridou, Lia Paschalia (My University, 2023)
Journalism has always been shaped by technology (Pavlik, 2000); however, the changes brought about by increasing automation and algorithms are having a profound impact on how news is produced and consumed (Thurman, Lewis & Kunert, 2019). More specifically, automation techniques and algorithmic technology are (re)shaping content production by means of automated storytelling, data mining, news dissemination and content optimization (Diakopoulos, 2019). This study sets out to illuminate how algorithms can enhance story telling capabilities for the production of feature stories. A common thread of criticism associated with online stories is their offering fragmented bits of information (Eveland, 2003) and reproducing news stories, the so-called phenomenon of churnalism (Saridou, Spyridou & Veglis, 2017). Recent work (Andersen & Strömbäck, 2021) concludes no general learning effects from online outlets (as opposed to offline media), a finding raising serious questions regarding a broadly informed citizenry in the web 3.0 era. A key question thus is how, under severe time pressures imposed by the new media ecosystem, should professional agency and algorithms be blended together in order to efficiently and effectively produce news stories which contain a diversity of sources and views and avoid repetition and banal positioning. The study draws data from the collaboration of JECT.AI and SigmaLive. JECT.AI is a company which has produced a tool enabling journalists to discover a multitude of relevant sources and data, and thus positions, during content creation on a real-time basis. Guided by the framework of professional ideology, and using qualitative data based on interviews with journalists who used the tool to produce content, this study provides evidence on the changing constituents of professional ideology in reference to the evaluation of JECT.AI, a computational news discovery (CND) tool. Findings indicate a major paradigm shift: the increased technologization of the newsroom manifested in tools using algorithms, data, and metrics, and the network logic of the platforms affecting news production and dissemination is cancelling out autonomy, a key boundary marker of professional journalism against commercial pressures. In contrast to previous research supporting journalists’ discomfort with technology’s disruptive impact on professional autonomy and judgement, our findings suggest a well-accepted reduction of autonomy compensated by performance gains raising questions about editorial agency and knowledge-generation in the digital era.
Keywords: Technologization; Newsroom